Knowledge creation cycle impact project success: work experience and position as moderator variables. (18th November 2022) - Yousefi, Farzaneh; Momeni, Ehsan; Jahanian, Elham
One of the main problems of organisations has always been the lack of adequate consideration about employees' knowledge. In this regard, the importance of this factor in project-oriented firms can be a debatable subject. This article aimed to respond on how project success can be influenced by the knowledge creation process. This quantitative study was conducted based on the questionnaire, and confirmed through face validity and constructs validity. Two hundred thirty-four managers and employees from the National Iranian Copper Industries Company as a project-oriented organisation participated in this study. Analysing the data depicted that there was a positive relationship between the knowledge creation processes (0.697) and project success, and, work experience has a moderator effect on the hypothesis. By implementing the knowledge creation cycle, in the way of paying attention to the current knowledge and information, project-based organisations can enhance the success of projects.